What do older people who have attempted suicide experience? Study protocol for a qualitative meta-synthesis among older adults, family caregivers and healthcare professionals - Hui Luo; Xin Zhou; Cheng Lei; Kejimu Sunzi; Yadi Li (BMJ Open)
Introduction Attempted suicide among older adults represents a significant mental health concern that has witnessed a rising incidence within this demographic in recent years. Research indicates that attempted suicide among the older population serves as a primary risk factor for completed suicide. Consequently, the objective of this study is to provide a comprehensive overview of the prevailing factors that influence suicide attempts among older adults, thereby offering evidence to guide healthcare professionals in designing targeted interventions.Methods and analysis This study will adhere to the Joanna Briggs Institute framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. We will synthesise qualitative studies using a comprehensive and inclusive bibliographic search strategy. The following databases will be searched: PubMed, Embase, Web of Science, CINAHL and the Cochrane Library. The quality of the articles will be assessed using the 10-item Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research. At the same time, data extraction will be performed using the Qualitative Assessment and Review Instrument data extraction form proposed by the Joanna Briggs Institute for Evidence-Based Practice. The synthesis of findings will adhere to the principles and procedures of Thomas and Hardens' three-stage thematic synthesis approach.Ethics and dissemination Ethical approval will not be required for this study, as it solely encompasses data derived from previously published research. The findings will be disseminated through publication in a peer-reviewed journal. Moreover, the results will be presented at relevant academic conferences to guarantee that the study’s outcomes reach pertinent stakeholders. This protocol is registered with the PROSPERO prospective database for systematic review.PROSPERO registration number CRD42023408385.